Feasibility of using the P-Cable high-resolution 3D seismic system in detecting and monitoring CO2 leakage. (March 2021) - Waage, Malin; Singhroha, Sunny; Bünz, Stefan; Planke, Sverre; Waghorn, Kate A.; Bellwald, Benjamin
Highlights: 4D studies of P-Cable HR3D data show good repeatability and a monitoring potential. The P-Cable system can detect very small subsurface CO2 leaks (1.3–10.6 t). We conclude that the system can be valuable in monitoring the (shallow) subsurface. Abstract: The P-Cable technology is an acquisition principle for high-resolution and ultra-high-resolution 3D seismic data. Many 3D seismic datasets have been acquired over the last decade, but the application in time-lapse studies for monitoring of CO2 storage is a new and intriguing topic. High-resolution 3D (HR3D) seismic has the potential to detect and monitor CO2 leakage at carbon capture and storage sites with higher accuracy at depths ∼0−2 km below the seafloor compared to more traditional conventional seismic time-lapse data. Here, we synthesize and evaluate research on detection of subsurface CO2 movement using the P-Cable system and address the comparative advantages and disadvantages of conventional and HR3D technologies for subsurface fluid migration monitoring. Studies on P-Cable 4D seismic data show good repeatability (NRMS, 10–40 %), indicating a future monitoring potential. Analysis of detection limits of CO2 data from a CO2 storage site show the ability to detect very small amounts of CO2 (1.3–10.6 t; 3.3–27.4 % gas saturation) in the shallow subsurface. These detection limits are ∼30−300 times smaller than the detection limits of conventional seismic data at similar depths. We conclude that the P-Cable acquisition system can be a valuable monitoring tool in detecting small leakages and can complement conventional seismic data monitoring of the deeper interval.